Seasonal variations of microbes in particulate matter obtained from Dhaka City in Bangladesh. Issue 1 (1st January 2021) - Gulshan, Jahan-E-; Hossain, Shahid Akhtar; Hossain, Mohammad Enayet; Islam, Md Mominul; Emon, Sharmin Zaman; Manzum, Amika Ahmed; Jashim, Zuairia Binte; Nurul Huda, Muhammad
ABSTRACT: The present study, for the first time, evaluated the seasonal variation of PM10 -associated bacterial and fungal concentrations at four locations (CARS premises, Doyel Chattar, Postogola, and Chittagong Road) in Dhaka, Bangladesh. In this study, PM10 samples were collected four times on 20.3 × 25.4 cm irradiated glass fibre filter from November 2018 to August 2019. The concentrations of total airborne bacteria (14, 073 ± 8, 897 CFU/m 3 ) were found to be significantly higher (one-way ANOVA; p < 0.05) in Chittagong Road, which is known for traffic congestion, than that of the other locations. The total airborne bacterial concentrations occurred in the following descending order: winter>spring>summer>rainy. Bacillus spp. and Staphylococcus spp. were found to be the dominant species present in PM10 particles. Based on Pearson correlation analysis and stepwise multiple-regression analysis, relative humidity was found to be the most important variable controlling the concentrations of total airborne bacteria. Common fungi such as Aspergillus, Penicillium, Cladosporium and Fusarium genera were identified in the PM10 samples. The highest fungal concentration (1, 974 ± 1, 173 CFU/m 3 ) was found at Chittagong Road. The total fungal spore concentrations occurred in the following descending order: summer>spring>winter>rainy. From correlation analysis and stepwise regression analysis, the temperature was found to be the most important variable influencing the concentrations of fungi in PM10 samples. A dose-rate estimation study revealed that the children were more vulnerable compared to adults with respect to exposure to bacterial and fungal dose rates. The present study has enormous implications considering the health hazards the bacterial and fungal communities pose to humans.